Integrative study of Islamic education learning from a progressive Islamic perspective at SMP Muhammadiyah - Saibah, Saibah; Nursa, Ruri Afria (Early Publishing, 2025)
The essence of Islamic Education, apart from the transfer of values and knowledge, is also one of the forms of morals human, it is necessary to keep up with current developments. The aim of this research is to examine in an integrative manner the learning of Islamic religious education with a progressive Islamic perspective in an inclusive concept in Muhammadiyah secondary schools. This research method uses Field Research. and collection techniques using observation, interviews and documentation, documents, books which are in line with this research. The concept of progressive Islam is centered on four aspects, namely liberation, humanization, transcendence, emancipation. The results of this research are generally comprehensive and in learning Islamic Religious Education from a progressive Islamic perspective in schools, namely (1) learning Islamic Religious Education from a Progressive Islamic Perspective at SMP Muhamamdiyah fully implements the values of liberation, humanization, transcendence and emancipation which are integrated into inclusive and progressive Islamic Education at the school (2) SMP Muhammadiyah implements Inclusive Learning of Islamic Religious Education from an Islamic perspective Progress still needs to be improved in terms of integration between one scientific field and another